Comprehending the relationship between a company and its accountants, 1894–1967: Evaluating and accommodating Foucauldian and other perspectives. (August 2020) - Ding, Ying Yong; McKinstry, Sam; Su, Peiran; Kininmonth, Kirsten
This article analyses the relationship between a Scottish manufacturing company and the accountancy firm which provided it with professional services across its existence (1894–1967). It examines the professional roles fulfilled by the accountants, the work done and the fee income derived from it, in the context of the company's history. It emphasises the importance of the services provided by accountancy firms for unlisted companies in understanding the development of professional accountancy in the United Kingdom. The material presented is used to test three different explanations of the UK accountancy profession's rise which relate to the auditing function and has implications for historical methodology and epistemologies. The explanations explored may be categorised as economic rationalist, Foucauldian and jurisdictional points of view.